Dynamics and Control of Advanced Structures and Machines 2019
DOI: 10.1007/978-3-319-90884-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Contour Motion of Belt Drive by Means of Nonlinear Rod Approach

Abstract: The contour motion of the belt drive, i. e. the motion with the constant trajectory is addressed. The belt is considered as a closed Cosserat line whose particles have translational and rotational degrees of freedom. The problem is considered in the framework of geometrically nonlinear formulation with no restrictions on the smallness of displacements and rotations. The spatial (Eulerian) coordinate which is the arc coordinate in the actual configuration is introduced. The belt is divided into four segments: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In recent related works on the topic (see [2,8]), we find similar formulations with large displacements and rotations. However, the authors of [8] use some simplifying assumptions in the contact segment.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…In recent related works on the topic (see [2,8]), we find similar formulations with large displacements and rotations. However, the authors of [8] use some simplifying assumptions in the contact segment.…”
Section: Introductionsupporting
confidence: 72%
“…However, the authors of [8] use some simplifying assumptions in the contact segment. The friction interaction is assumed to occur at the belt's middle axis, whereas in the papers [2,6] it is at the bottom fibers. Shifting the contact forces to the belt's middle axis leads to certain simplifications in the problem formulation, for instance, to constant stretch in the sticking region.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have demonstrated that the concentrated contact interaction is a limiting case of the distributed sliding friction interaction, when the sliding zone collapses into a single point because of the high friction force. Future finite element solutions for the steady state dynamic problem for a closed belt drive as well as the numerical integration of the boundary value problem similar to [4, 32] will be based on the above theoretical results and techniques of modeling.…”
Section: Resultsmentioning
confidence: 99%
“…Smallness of the creep (sliding) zones in belt drives at realistic operation conditions makes it desirable to develop an idealized model with perfect adhesion (no-slip condition) on the entire contact surface similar to the previous analysis with the string model [14, 30, 33]. The attempt to extend the static equations to the case of a moving belt [3] and to solve the resulting boundary value problem [4] has not succeeded so far. Trying to solve the problem using various finite element schemes, we arrived at the conclusion that its formulation is probably incomplete without the consideration of concentrated contact forces in the touching points.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of discrete belt models have been presented in [15,21,22]. Non-discrete belt models can be modelled as an elastic rod (papers [3,4,29]), a string with assumed longitudinal and bending stiffness (papers [9,11,28] and [30]). Of course, regardless of the adopted belt models and models of friction at the belt-pulley contact, there is always a need to adjust the number of coefficients adopted in them, which will ensure the compatibility of these models with the real object.…”
Section: Introductionmentioning
confidence: 99%